3(10x-2)=-4(-7x+11)

Simple and best practice solution for 3(10x-2)=-4(-7x+11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(10x-2)=-4(-7x+11) equation:


Simplifying
3(10x + -2) = -4(-7x + 11)

Reorder the terms:
3(-2 + 10x) = -4(-7x + 11)
(-2 * 3 + 10x * 3) = -4(-7x + 11)
(-6 + 30x) = -4(-7x + 11)

Reorder the terms:
-6 + 30x = -4(11 + -7x)
-6 + 30x = (11 * -4 + -7x * -4)
-6 + 30x = (-44 + 28x)

Solving
-6 + 30x = -44 + 28x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-28x' to each side of the equation.
-6 + 30x + -28x = -44 + 28x + -28x

Combine like terms: 30x + -28x = 2x
-6 + 2x = -44 + 28x + -28x

Combine like terms: 28x + -28x = 0
-6 + 2x = -44 + 0
-6 + 2x = -44

Add '6' to each side of the equation.
-6 + 6 + 2x = -44 + 6

Combine like terms: -6 + 6 = 0
0 + 2x = -44 + 6
2x = -44 + 6

Combine like terms: -44 + 6 = -38
2x = -38

Divide each side by '2'.
x = -19

Simplifying
x = -19

See similar equations:

| -(41p-82q+80)= | | -42=2(7n+7) | | 2(5t-3)=3(2t+6) | | 5(2x-z)=7h | | x^3+2x^2-8x-16=0 | | 5(x-5)=x(14-4) | | 5(2x-4)=2(3x+2) | | -7(p+7)=-21 | | 38+x=2(11+x) | | 4(3x-5)=2(x-5) | | 6(m+3)=2(m-1) | | -1-x^2=0 | | 56=-8(1+n) | | 0=4+2x-2x | | 2(4x+3)=3(2x+4) | | -(v+6)=-14 | | x^2+36x=0 | | 3(2x-3)=5(x+1) | | 8(x+9)=8x+72 | | 3x-2y-4=7y+6 | | 3x-5=x^2 | | (x+4)(2x+1)=(2x+5)(2-x) | | 27x+9=3x+30+3x | | A=1/2*70(40+160) | | 13m+3n-6m+9n= | | -4x^2-12x-3=0 | | (x+0.6)(x+1.6)=0 | | y=-16x^2 | | (2x-3)*(x+5)+7=(x-4)*(2x-1)+20 | | 7x^3+y^3+3xy(x-y)-12x^2+6x=1 | | 4x-(x+3)=(2x+5) | | (2x-3)*(x+5)+7=(x-4)*(2x-1)+2 |

Equations solver categories